Menyelesaikan Konflik Kerukuan Umat Beragama Dengan Hati - Mashudi, Mashudi (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
This paper tries to uncover the alleged conflict regarding the building of the church in the village of the Dermolo Kembang District Jepara Regency precarious and prone to conflict ended with shade. Also who those parties are considered to play a role in the effort to create a conducive climate. As a result, first, in order to optimize the role of religious institutions to manage the plurality of fine, completion of religious harmony in the village Dermolo Jepara regency using hearted approach, meaning invited intensive communication and sit down with all parties on a regular basis until otherwise completed while wary lest result of the agreement provoked by the person who does not like the conditions of security and peace. Second, community, religious leaders, and religious institutions play an important role in creating such harmony.